[WITHDRAWN] Factors influencing water access for livestock by pastoralists in semi-arid areas in Monduli District Tanzania - Mfinanga, Fredrick Alleni; Msuya -Bengesi, Catherine Phillip; Madaha, Rasel Mpuya (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2023)
The study examines factors influencing the level of water access for livestock in semi-arid areas of Monduli District, Arusha Region Tanzania. The cross-sectional research design was applied to collect data from a sample of 367 randomly selected pastoralist households. The data was collected using semi-structured questionnaire, focus group discussions, and documentary review. Quantitative data were analysed by using inferential statistics including chi-square tests and ordinal logistic regression model and descriptive statistics involved the use of frequency and percentage. Qualitative data was analysed by using content analysis. The findings show that the majority accounting for 76.3 % of the pastoralist households experienced low level of water access for livestock and a few of them accounting for 2.5% had high water access for livestock. Additionally the findings indicate that off-farm income, access to credit, access to subsidies and the use of donkeys were the factors influencing the level of water access for livestock. The study calls on the policy-makers to establish pro-poor interventions for livestock water supply in the pastoral communities.JEL Classification I30; O13; Q12